2022
DOI: 10.3390/biomedicines10082041
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Idiopathic Arthritis, Uveitis and Multiple Sclerosis: Description of Two Patients and Literature Review

Abstract: Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood, while multiple sclerosis (MS) is a demyelinating disease of the central nervous system, characterized by remission and exacerbation phases. An association between MS and rheumatologic diseases, in particular rheumatoid arthritis, has been described and numerous studies acknowledge anti-TNF-α drugs as MS triggers. Conversely, the association between MS and JIA has been reported merely in five cases in the literature. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Our patient's negative oligoclonal bands in addition to the "onion bulb" lesion discovered on MRI suggested that her condition was a demyelinating disorder distinct from MS. BCS physiopathology is unclear, although several mechanisms have been proposed [9]. A link between autoimmune disorders, such as JIA, and demyelination has been reported, but predisposing factors remain unclear [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's negative oligoclonal bands in addition to the "onion bulb" lesion discovered on MRI suggested that her condition was a demyelinating disorder distinct from MS. BCS physiopathology is unclear, although several mechanisms have been proposed [9]. A link between autoimmune disorders, such as JIA, and demyelination has been reported, but predisposing factors remain unclear [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to insufficient data, it is extremely difficult to determine what mechanism exists between the common course of JIA and MS. Potential methods of treatment still remain unknown and therefore present a great challenge for clinicians [8].…”
Section: Treatment Of Jia With Concurrent Ms In Young Patientsmentioning
confidence: 99%